Real-world effectiveness of the pegfilgrastim on-body injector in preventing severe neutropenia. (January 2022) - Maahs, Lucas; Tang, Amy; Saheli, Zaid Al; Jacob, Brigid; Polasani, Rishika; Hwang, Clara
Introduction: Granulocyte colony-stimulating factors are used in medical oncology for the prevention of neutropenia. On-body injectors (OBI) have an advantage over the traditional injection (TI) method of not requiring a second visit to the clinic, but these devices are subject to failure. The objective of this study was to assess the efficacy of OBIs in the real-world. Methods: Women with breast cancer diagnosed between June 2015 and June 2016 treated with cytotoxic chemotherapy and a granulocyte colony-stimulating factor were retrospectively identified from the medical records of Henry Ford Hospital. The primary outcome was the incidence of severe neutropenia (SN), defined as an absolute neutrophil count (ANC) ≤500. Secondary outcomes included incidence of neutropenia (ANC ≤ 1500), neutropenic fever, and mortality. A secondary analysis of the data was performed to identify predictors of SN. Results: A total of 837 cycles of chemotherapy were analyzed. The OBI was used in 395 cycles and the TI in 442. The OBI group had patients that were older, had higher baseline ANC, and were more often white. The incidences of SN, neutropenic fever and neutropenia were not different between groups. Patients with a lower baseline ANC and white ethnicity were at a higher risk for SN. AC (doxorubicin and cyclophosphamide) was the most commonly used chemotherapy regimen (38% of total cycles). Conclusions: There was no difference in the efficacy of the OBI and TI methods for preventing SN, neutropenic fever and neutropenia.